Guillain Barré syndrome and Coronavirus infection / Síndrome de Guillain Barré e infecção por Coronavírus - Bernis, Eduarda Heringer (2022)
The coronavirus (COVID-19)  pandemic is a major problem of public health worldwide since 2020. The virus that first started causing pneumonia in Wuhan, China, has spread throughout all six continents and is now also known for causing other health issues, including neurological infection. In the last months, there were many case reports of Guillain-Barré Syndrome (GBS) in patients with SARS-CoV-2 infection, raising concerns over a possible association. The coronavirus infiltrated in neuronal tissue is able to modify the pathophysiology of GBS, that is a polyneuropathy and also an autoimmune disease, commonly triggered by infections of the human body. Acute inflammatory demyelinating polyneuropathy (AIDP) is one of the most common types of demyelinating polyneuropathy,  causing loss of the myelin sheath, what makes electrical messages cannot travel between the brain and the periphery of the body. This association must be early diagnosed so that the physician  can manage it to avoid respiratory depression and other consequences of the condition.